THE EFFECT OF APPLYING SELF-CENSORSHIP ON THE ADMINISTRATIVE SYSTEM IN THE ARAB ISLAMIC STATE - Assist Prof Dr. Sohaib Mohammed Naser (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study deals with the issue of the impact of applying self-censorship on the administrative system in the Arab Islamic State, and reviews the concepts of censorship throughout its historical eras and the development of its apparatus, which have existed for more than fourteen centuries. The research aims to clarify the role of Islam in the concept of censorship and rooting its concepts and principles circulating in the field of self-censorship and its impact on the administrative system throughout its historical ages.